Інструментальні засоби непараметричної ідентифікації нелінійних динамічних систем на основі моделей Вольтерра у частотній області - Pavlenko, Vitaliy Danylovich; Cperanskiy, Victor Olexandrovich (Kamianets-Podilskyi National Ivan Ohiienko University, 2014)
The software-hardware tools used for nonlinear dynamical systems nonparametric identification based on Volterra models in frequency domain are presented. The polyharmonic test impacts are selected as the test ones. The proposed methodology and the toolkit are used for building the communication channel model